THE INTERSECTION OF TRI HITA KARANA VALUES AND FRAUD HEXAGON THEORY IN CORPORATE ACCOUNTING ETHICS - Putri Prawitasari, Putu; Budiadnyani, Ni Putu; Aprilyani Dewi, Putu Pande R. (AKUNTANSI DEWANTARA, 2025)
This paper examines the intersection of the Tri Hita Karana values and the Fraud Hexagon Theory to promote ethical conduct in corporate accounting. The Tri Hita Karana, a Balinese philosophy, emphasizes the harmonious relationship among individuals, the community, and the divine, offering a holistic approach to ethical decision-making. Through a comprehensive literature review, the study explores the potential synergies between these two frameworks. The findings suggest that integrating the Tri Hita Karana values, such as piety, social harmony, and environmental stewardship, can complement and enhance the Fraud Hexagon Theory, which identifies six key factors contributing to fraudulent behavior. Scopus databased sources are utilized to analyze the practical implications and provide recommendations for corporate leaders, accountants, and policymakers to foster a culture of ethical conduct in the accounting profession. The paper presents a conceptual framework to foster a corporate culture prioritizing ethical accounting practices, strengthening the resilience of the financial sector against fraud. This synthesis can inform the development of robust corporate governance policies, employee training programs, and ethical leadership initiatives, ultimately promoting a culture of integrity and accountability within the accounting profession. By exploring the intersection of these frameworks, the paper aims to provide a more holistic approach to addressing the complex issue of accounting fraud, with implications for businesses, investors, and the broader financial ecosystem.